Measuring improvement in knowledge of drug policy reforms following a police education program in Tijuana, Mexico - Arredondo, J. (Harm Reduct J, 2017)
BACKGROUND: Mexico’s 2009 “narcomenudeo reform” decriminalized small amounts of drugs, shifting some drug law enforcement to the states and mandating drug treatment diversion instead of incarceration. Data from Tijuana suggested limited implementation of this harm reduction-oriented policy. We studied whether a police education program (PEP) improved officers’ drug and syringe policy knowledge, and aimed to identify participant characteristics associated with improvement of drug policy knowledge. METHODS: Pre- and post-training surveys were self-administered by municipal police officers to measure legal knowledge. Training impact was assessed through matched paired nominal data using McNemar’s tests. Multivariable logistic regression was used to identify predictors of improved legal knowledge, as measured by officers’ ability to identify conceptual legal provisions related to syringe possession and thresholds of drugs covered under the reform. RESULTS: Of 1750 respondents comparing pre- versus post training, officers reported significant improvement (p < 0.001) in their technical understanding of syringe possession (56 to 91%) and drug amounts decriminalized, including marijuana (9 to 52%), heroin (8 to 71%), and methamphetamine (7 to 70%). The training was associated with even greater success in improving conceptual legal knowledge for syringe possession (67 to 96%) (p < 0.001), marijuana (16 to 91%), heroin (11 to 91%), and methamphetamine (11 to 89%). In multivariable modeling, those with at least a high school education were more likely to exhibit improvement of conceptual legal knowledge of syringe possession (adjusted odds ratio [aOR] 2.6, 95% CI 1.4–3.2) and decriminalization for heroin (aOR 2.7, 95% CI 1.3–4.3), methamphetamine (aOR 2.2, 95% CI 1.4–3.2), and marijuana (aOR 2.5, 95% CI 1.6–4). CONCLUSIONS: Drug policy reform is often necessary, but not sufficient to achieve public health goals because of gaps in translating formal laws to policing practice. To close such gaps, PEP initiatives bundling occupational safety information with relevant legal content demonstrate clear promise. Our findings underscore additional efforts needed to raise technical knowledge of the law among personnel tasked with its enforcement. Police professionalization, including minimum educational standards, appear critical for aligning policing with harm reduction goals.